Analisa Pengaruh Brand Image, Brand Trust dan Economic Benefit Terhadap Niat Pembelian Polis Asuransi PT. Sequislife di Surabaya - Tandun, Calvin (Jurnal Strategi Pemasaran, 2014)
This research is conducted to find the effect of brand image, brand trust and economic benefit on purchase intention toward Insurance product of PT. Sequislife in Surabaya. The samples in this study are those who had received an offer to buy an insurance polis of Sequislife in Surabaya. Respondents used as samples in this study are 91 persons. The method of analysis used in this study is multiple linear regression analysis. The analysis show that the brand image, brand trust and economic benefit simultanously give significant effect on customer purchase intention towards insurance products of PT. Sequislife in Surabaya. However, only brand image that has a significant negative effect on purchase intentions individual insurance policies in PT. Sequislife in SurabayaÂ